Fieldwork at sunset: Visual representations of anthropology online - Goodwin-Hawkins, Bryonny; Gould, Hannah (Focaal, 2020)
Most institutional anthropology departments have a website, to tout credentials, attract students, and offer information. These websites also take up the visual task of disciplinary representation, but their images have skipped the scrutiny that is necessary and overdue. This article analyzes online images of sociocultural anthropology across one hundred high-ranking universities worldwide. We show how, online, a discipline defined by diversity becomes readily reducible to "exotic" geographies and objectified "others." While the urban serves as an unattractive foil, frequent images of children recall charity campaigns. Such visual tropes--which comprise a significant, public interface for anthropology--are not just awkwardly dated but also do disservice to ambitions for public anthropology. Change, we suggest, must begin at (the) home(page). Keywords: photography, public anthropology, visual anthropology, websites